Salivary gland pleomorphic adenoma in the Netherlands: A nationwide observational study of primary tumor incidence, malignant transformation, recurrence, and risk factors for recurrence. (March 2017) - Valstar, M.H.; de Ridder, M.; van den Broek, E.C.; Stuiver, M.M.; van Dijk, B.A.C.; van Velthuysen, M.L.F.; Balm, A.J.M.; Smeele, L.E.
Highlights: The standardized incidence rate (ESR) of SGPA is 4.2–4.9 per 100, 000 person years. Women show a higher, increasing incidence and bimodal age distribution of SGPA. The 20-year recurrence rate was 6.7%. Secondary malignant transformation 0.15%. Positive or uncertain margins and lower age showed a higher odds of recurrence. Tumors situated in the minor glands had a lower odds of recurrence. Abstract: Introduction: Whereas salivary gland pleomorphic adenoma (SGPA) is the most common type of salivary gland tumor, little is known about its epidemiology because national cancer registries do not register this disease. Objectives: To establish SGPA incidence trends, rates of secondary malignant transformation and recurrence and associated factors in the Netherlands. Materials and methods: Data on incidence, epidemiology, secondary malignant transformation and recurrence were retrieved from the Dutch pathology registry (PALGA) for the years 1992, 1997, 2002, 2007, and 2012. Multivariate analysis was performed to discover the risk factors for recurrence. Results: 3506 cases of SGPA were recorded implying an overall European standardized rate of 4.2–4.9 per 100, 000 person-years. Our figures showed a female preponderance (1:1.43) with an annual 1% rise in female incidence (95% confidence interval [CI]: 0.2–1.8) and a bimodal age distribution in women (p < 0.0001). The overall 20-year recurrence rate was 6.7%, and median time to first recurrence was 7 years. Positive and uncertain resection margins and younger age at diagnosis were risk factors for recurrence, with odds ratios (ORs) of 4.62 (95%CI 2.84–7.51), 4.08 (95%CI 2.24–7.43), and 0.42 (95%CI 0.29–0.63) respectively. Tumor locations in the minor salivary glands had lower odds of recurrence than tumors in the parotid (OR 0.24; 95% CI: 0.07–0.77; p < 0.016). Malignant transformation occurred in 0.15% of SGPAs (3.2% of recurrences). Conclusion: This first nationwide study clearly showed sex differences in SGPA epidemiology, possibly suggesting some underlying hormonal mechanism. Long-term recurrence risks were low, and secondary malignant transformation risks were very low.